Birth Length, Exclusive Breastfeeding History, and Complementary Feeding History as Risk Factors for Stunting in Toddlers 12-24 Months of Age in the Tambakrejo Sidoarjo Health Centre Working Area - Zal Zabella Ika Saputri; Taufiqurrahman Taufiqurrahman; Nur Hatijah; Ani Intiyati (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Stunting is form of chronic malnutrition still occurs in Indonesia. This condition occurs children with height/age values below -2SD. Describe birth length, exclusive breastfeeding history, complementary feeding, also incidence of stunting in toddlers at Tambakrejo Sidoarjo Health Centre. Type research descriptive research with sample 60 children aged 12-24 months. History birth length was obtained by MCH book, data history exclusive breastfeeding and complementary foods was obtained by questionnaire, and data incidence of stunting gained by measuring height. Toddlers with PBLR had 14 times higher risk being stunted compared to toddlers with PBLN (p=0.001; OR=14), toddlers with history of Not Exclusive Breastfeeding had 0.609 times smaller risk of being stunted than toddlers with history of Exclusive Breastfeeding (p=0.567; OR=0.609), toddlers with history of poor complementary feeding had 0.060 times smaller risk of being stunted than toddlers with history of good complementary feeding (p=0.004; OR=0.060). There substantial correlation between birth length and history of complementary feeding as risk factor for stunting in children aged 12-24 months in Tambakrejo Sidoarjo Health Centre. There is no substantial correlation between exclusive breastfeeding history risk factor for stunting in toddlers aged 12-24 months in Puskesmas Tambakrejo Sidoarjo. Health workers can intervene and improve nutrition programmes related.